Cork: sustainability and new applications - Gil, Luís (2016)
Cork is a strategic material used in multiple applications and its use has accompanied mankind since the days of Ancient Egypt. The cork oak forests are extremely well adapted to the semi-arid regions of southern Europe and northern Africa (western Mediterranean). These forests help to prevent the advance of desertification, improve water penetration into the soil and hydrological regulation, promote soil conservation, and being the perfect habitat for many animal and vegetables species. Consequently, these forests promote biodiversity. Save the cork forests, increasing the area and the quantity and quality of cork produced and develop new products with high added value are essential actions. The loss of the economic importance of the cork activity would lead to an uncertain future of cork oak forests, promoting biodiversity loss, land abandonment (social desertification), and also social imbalance. This could lead to the disappearance of one of the most sustainable industries based on forest products, beyond the environmental and nature problems created. One of the ways to decrease the amount of carbon dioxide in the atmosphere is the production of long-life products based on plant biomass, which include without doubt, cork products. Furthermore, these materials are “carbon neutral” at the time of decomposition or energy recovery.